A Study of Foreign Body Aspiration in Children - Bakal, Unal; Keles, Erol; Sarac, Mehmet; Karlidag, Turgut; Kaygusuz, Irfan; Kazez, Ahmet (Lippincott Williams & Wilkins, 2016)
Aim: To analyze diagnostic and therapeutic methods used in the diagnosis and treatment of foreign body aspiration (FBA) and to determine the impact of technical infrastructure on mortality and morbidity. Methods: Hospital records of patients diagnosed with FBA between the years 1987 and 2015 were retrospectively evaluated. The patients were grouped according to the length of time until their admission to the hospital as follows: Group I (0-24 h); Group II (1-7 days); Group III (>7 days). Age, sex, history, existing symptoms, physical examination, endoscopic and radiological findings, time to treatment, type and location of the foreign body, treatment modality, mortality and morbidity rates were recorded. A rigid bronchoscopy procedure was performed between 1987 and 2005 (Phase 1) without the need for an optic telescope, while between 2006 and 2015, it was performed using a rigid bronchoscope equipped with an optical telescope and HD camera (Phase 2). Results: A total of 513 patients [male, n = 328 (63.9%) and female, n = 185 (36%)] who had complaints of FBA were evaluated. The mean age of the patients was 3.7 +/- 3.5 years. In order of decreasing frequency, sunflower seeds, peanuts, and hazelnuts (38% of all patients) were extracted. Bronchoscopy could not detect a foreign body in 127 (24.7%) patients. Foreign bodies were mostly observed in the right (43.3%) main bronchus. When the locations of the foreign bodies were analyzed, significant differences were found for subglottic foreign bodies (FBs) between Groups I and III and for FBs located within the bifurcation between Groups II and III. The most prevalent symptom was sudden onset of coughing in 231 (45%) patients. A significant difference was detected between Groups I and II, as well as Groups I and III, for sudden onset of coughing, decrease in breathing sounds, wheezing, and fever. No abnormal radiological signs were detected in 136 (26.5%) patients. Manifestations of emphysema were significantly more frequent in Group I, pneumonia in both Groups II and III, and pleural effusion in Group III. When complications related to bronchoscopy were evaluated, a significant increase was observed in transient complications in Group III compared with Groups I and II. The negative bronchoscopy rate in Phase I was statistically significantly higher than that in Phase II. Conclusions: When the length of time elapsed till admission to a hospital was considered, a decrease in morbidity rates was observed in patients who presented at a hospital within the first 24 hours. In the diagnosis of suspect patients, virtual bronchoscopy seriously decreased the incidence of negative bronchoscopy. The authors determined that for bronchoscopic procedures, the renewal of technical ultrastructure with technological advances strongly contributed to a decrease in mortality and morbidity as a result of FBA in paediatric patients.
Keywords: Foreign body aspiration; morbidity; mortality; paediatric age; virtual bronchoscopy